Implementasi Model Pembelajaran Bamboo Dancing dalam Meningkatkan Hasil Belajar PAI Siswa di SMPN 7 Bengkalis Riau - Atira Rossa; Ika Kurnia Sofiani; Muhajir Darwis (Indonesian Journal of Islamic Education Studies (INJURIES), 2024)
This research was motivated by the fact that the learning methods used were still less effective, resulting in students tending to be less motivated in the learning process. The aim of this research is to find out how the Bamboo Dance learning model is implemented and to find out whether the implementation of the bamboo dance learning model can increase students' learning motivation in class VII PAI subjects at SMPN 7 Bengkalis. The type of research used in this research is experimentation by taking 2 classes from the population consisting of an experimental class and a control class. The total sample in this study was 49 students divided into 2 classes, namely class VII A as the control class and VII B as the experimental class using the Total Sampling technique. Data collection techniques use tests and documentation. The results of the research are that after implementing the Bamboo Dance learning model, students learn to run well, this is because students are more active in discussing, asking questions, exchanging information and paying attention to the material being explained. Furthermore, the results of the research are the results of the paired sample t test which was carried out by the researcher on the results of the sig<t table, namely 0.000<005, which means there has been a significant change. The test results also show a difference in the average scores of the experimental posttest and control posttest, namely the experimental is 84.58 while the control is 80.60. From these results it can be concluded that the Bamboo Dancing learning model can improve student learning outcomes in class VII PAI subjects at SMPN 7 Bengkalis. Keywords: Learning Model; Bamboo Dance; Learning Outcomes